(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the outcome and factor affecting the periapical surgery performed in endodontic and in oral surgery units of a teaching dental hospital. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at the Bibi Aseefa Dental College, Larkana from January 2019 to January 2021 in two year duration. Materials and Methods: Study was conducted on 120 patients, half of them 60 patients were operated by endodontist and half 60 patients were operated by oral surgeon. Success rate and failure of radiographic and clinical outcomes were main outcomes. SPSS version 23 was used for data analysis. Tests of significance (t-test and chi square test) were applied. P value ≤0.05 was considered as significant Results: Good periapical surgery was noted as 61.5% and 70.2% in successful and unsuccessful patients, respectively. Good coronal seal noted in 84.6% and 87.2% in successful and unsuccessful patients, respectively. Post was observed in 50.0% successful patients. No difference was statistically significant Conclusion: There is no significant difference regarding radiographic and clinical success and failure between periapical surgery in endodontic and oral surgery units. Quality of filling and filling material are two main contributing factors of periapical surgery.